CONTENTS AND MAIN POINTS OF THE TECHNOLOGY FOR THE PREVENTION OF FUNCTIONAL DISORDERS OF THE MUSCULOSKELETAL APPARATUS OF YOUNG BASKETBALL PLAYERS, TAKING INTO ACCOUNT THE LEVEL OF STATE OF THE BIOGEOMETRIC POSTURE PROFILE - Nevolin, D. A.; Mikhailenko, R. I.; Nalyvaichenko, L. Yu. (Rehabilitation and Recreation, 2024)
The aim was to substantiate the contents and basic points of the technology for the prevention of functional disorders of the musculoskeletal apparatus of young basketball players, taking into account the level of the state of the biogeometric profile of the posture. Laying a fundamental basis for the development of physical qualities, technical preparedness, and functional conditions is important at the initial stage of multi-year improvement in modern sports. Experimental studies were held at the Department of Theory and Methodology of Physical Education of Vasyl Stefanyk Precarpathian National University in the period from September 2022 to August 2024. The experiment involved 66 basketball players aged 9-10 years of the children's and youth sports school in Ivano-Frankivsk, previously having received their parents' consent to analyze data from medical records. The research was held in compliance with the requirements of the WMA Declaration of Helsinki – Ethical Principles for Medical Research Involving Human Participants. Research methods: theoretical - for studying and substantiating the basic points of the research, outlining its problem area; empirical: pedagogical observation as a method of empirical level of research - for familiarization with the process of organizing educational and training classes. The "Torso" program was used to determine posture types; pedagogical experiment; methods of mathematical statistics. The results. The content of the strategy for the correction and prevention of disorders of the posture of young basketball players will be aimed at the stage of initial training, when the task of sports selection and sports orientation of young athletes is solved. This is of great importance, first of all, for the optimization of the structural reconstruction of the spine under the pressure of physical exertion and the prevention of vertebrogenic diseases, since such factors as early specialization, intensification of training, limitation of motor activity by the distance education, lead to the delineation of contradictions between the increased requirements for the preparedness of young athletes, related to the need for systematic growth of results, and limited functional capabilities of their body. The basic elements of the author's technology were: the conceptual basis of training basketball players aged 9-10 years at the stage of initial training (2nd year of training); theoretical and methodological approaches to correction and prevention of postural disorders of young athletes. Conclusions. The outlined theoretical and methodological approaches to the study of the problems of correction and prevention of postural disorders of young athletes and their graphic structure presented claim to be recognized as a paradigm of physical culture and sports rehabilitation as an element of the theory and methodology of young athletes preparation in certain sports.